A harmonized European training syllabus for thoracic surgery: report from the ESTS-ERS task force - (:unkn) unknown (OXFORD UNIV PRESS INC, 2018)
Training of European thoracic surgeons is subject to huge variations in terms of length of training, content of training and operative experience during training. Harmonization of training outcomes has been approached by creating the European Board of Thoracic Surgery, which has been accredited by the European Union of Medical Specialists (UEMS); however, a clear description of the content of training is lacking. Building on their recognized experience with curriculum building, task forces of the European Respiratory Society and the European Society of Thoracic Surgery agreed on a joint task force on training in thoracic surgery. The goal of this study is to report on the mission statement developed from the UEMS-driven survey, describe the Delphi method and the observed results and present the first large consensus-based syllabus. The working group is currently working on a description of the curriculum and assessment of learning outcomes.
Keywords: Surgical education; Training in thoracic surgery; Syllabus for thoracic surgery; Europe; CURRICULUM RECOMMENDATIONS; CORE SYLLABUS; HERMES; ONCOLOGY